Operative Outcomes of Single-Incision Laparoscopic Hysterectomy vs Conventional Laparoscopic Total Hysterectomy: A Prospective Randomized Controlled Study. (October 2022) - Fathi, Adel; Saleh, Mahmoud M.; Shetiwy, Mosab; Elzahaby, Islam A.; Farouk, Omar; Shams, Nazem; Elghandour, Mohamed F.; Abouzid, Amr
Background . Over time, there was an emerging need to shift from laparotomy to minimally invasive laparoscopic surgery, with the success of laparoscopic surgery in the last decade in gyne-oncology. Patients and Methods . This is a prospective randomized controlled trial conducted in Surgical Oncology Unit, Oncology Centre, Mansoura University, in the period between February 2016 and October 2019. Fifty female patients planned for total hysterectomy were randomized into two equal groups; the first underwent conventional laparoscopic hysterectomy (CLH), while the second underwent single-incision laparoscopic hysterectomy (SILH). Results. The mean operative time in the SILH group was 120.00 ± 28.72 minutes vs 103.20 ± 23.04 minutes in the CLH group ( P= .027). Median hospital stay in the SILH group was 1 day (range: 1–3 days), the same as that in the CLH group, with no statistical significance ( P = .384). Postoperative pain assessment using the Visual Analogue Scale (VAS) after 6 hours had a median score of 6 (2–8) in the SILH group and 6 (4–7) in the CLH group with significant increase in experienced pain in the SILH group ( P = .004), while no significant difference was noted after 12 hours and 24 hours in both SILH and CLH groups. Conclusion . Single-incision laparoscopic hysterectomy (SILH) has similar outcomes when compared to conventional laparoscopic hysterectomy as regard blood loss, hospital stay, conversion to laparotomy, intraoperative and postoperative complications with the disadvantages of longer operative time, increased surgeon's workload, and relatively more postoperative pain.